Interactions between amino groups in DNA. An Ab initio study and a comparison with empirical potentials - Sponer, J; Burcl, R; Hobza, P (Journal of biomolecular structure & dynamics, 1994)
An ab initio quantum chemical analysis of the close amino group contacts, existing in many DNA crystal structures, is presented. The calculations are made at the Hartree-Fock (HF) level with medium 6-31G* and 6-31G(NH2*) basis sets as well as with inclusion of correlation energy using the second order Møller-Plesset theory (MP2) with the 6-31G* basis set. We demonstrate that the model system (methylamine dimer, cytosine dimer) amino groups are forced to adopt significantly non-planar geometry to stabilize their mutual interaction. Comparison is made with a representative set of empirical potentials including AMBER, CHARMM and GROMOS. The empirical potentials are not reliable enough to analyze the amino group contacts occurring in the DNA double helices. We propose that the mutual amino group interactions contribute to the conformational variability of the CpG and ApT B-DNA steps.
Keywords: Cytosine; sekvence nukleotidů; Nucleic Acid Conformation; Dinucleoside Phosphates; molekulární sekvence - údaje; dinukleosidfosfáty; chemické jevy; Oligodeoxyribonucleotides; Chemical Phenomena; oligodeoxyribonukleotidy; konformace nukleové kyseliny; Chemistry, Physical; methylaminy; cytosin; fyzikální chemie; DNA; Methylamines; Molecular Sequence Data; Base Sequence